Expression of IGF-1 receptor and GH receptor in hepatic tissue of patients with nonalcoholic fatty liver disease and nonalcoholic steatohepatitis. (August 2022) - Osganian, Stephanie A.; Subudhi, Sonu; Masia, Ricard; Drescher, Hannah K.; Bartsch, Lea M.; Chicote, Mark L.; Chung, Raymond T.; Gee, Denise W.; Witkowski, Elan R.; Bredella, Miriam A.; Lauer, Georg M.; Corey, Kathleen E.; et al.
Abstract: Objective: The GH and IGF-1 axis is a candidate disease-modifying target in nonalcoholic fatty liver disease (NAFLD) given its lipolytic, anti-inflammatory and anti-fibrotic properties. IGF-1 receptor (IGF-1R) and GH receptor (GHR) expression in adult, human hepatic tissue is not well understood across the spectrum of NAFLD severity. Therefore, we sought to investigate hepatic IGF-1R and GHR expression in subjects with NAFLD utilizing gene expression analysis (GEA) and immunohistochemistry (IHC). Design: GEA ( n = 318) and IHC ( n = 30) cohorts were identified from the Massachusetts General Hospital NAFLD Tissue Repository. GEA subjects were categorized based on histopathology as normal liver histology (NLH), steatosis only (Steatosis), nonalcoholic steatohepatitis (NASH) without fibrosis (NASH F0), and NASH with fibrosis (NASH F1–4) with GEA by the Nanostring nCounter assay. IHC subjects were matched for age, body mass index (BMI), sex, and diabetic status across three groups ( n = 10 each): NLH, Steatosis, and NASH with fibrosis (NASH F1–3). IHC for IGF-1R, IGF-1 and GHR was performed on formalin-fixed, paraffin-embedded hepatic tissue samples. Results: IGF-1R gene expression did not differ across NAFLD severity while IGF-1 gene expression decreased with increasing NAFLD severity, including when controlled for BMI and age. GHR expression did not differ by severity of NAFLD based on GEA or IHC. Conclusions: IGF-1R and GHR expression levels were not significantly different across NAFLD disease severity. However, expression of IGF-1 was lower with increasing severity of NAFLD. Additional research is needed regarding the contribution of the GH/IGF-1 axis to the pathophysiology of NAFLD and NASH. Highlights: GH and IGF-1 have been implicated in the pathogenesis of NAFLD. Lower IGF-1 expression is associated with more severe NAFLD. Expression of IGF-1 and GH receptors is unchanged with increasing severity of NAFLD. The GH/IGF-1 axis is a potential therapeutic target in NAFLD.